METHODS OF TRAINING OF MODERN AIRCRAFT FLIGHT CREWS FOR INFLIGHT ABNORMAL CIRCUMSTANCES - Hryshchenko, Yurii; Romanenko, Viktor; Tronko, Vladimir; Hryshchenko, Yurii (Proceedings of National Aviation University (archive), 2017)
Purpose: The purpose of this article is the theoretical justification of the existing methods and development of new methods of training the crews of modern aircraft for inflight abnormal circumstances. Methods: The article describes the research methods of engineering psychology, mathematical statistics and analysis of the correlation functions. Results: The example of the two accidents of aircraft with modern avionics is shown in the problem statement. The pilot made a sharp movement of the steering wheel while go-around, which has led to a sharp diving and impossibility of coming out of it. It was shown that the developed anti-stress training methods allow crews to train a human operator to prevent such events. The theoretical solution of the problem of optimization of the flight on the final approach, considering the human factor, is suggested to solve using the method of analysis of the autocorrelation function. Conclusions: It is necessary to additionally implement methods of teaching the counteracting of factorial overlaps into the training course using the complex modern aircraft simulators. It is enough to analyze a single pitch angle curve of the autocorrelation function to determine the phenomena of amplification of integral-differential motor dynamic stereotype of the pilot.